The Application of the Arabic-Language Environment (Bi'ah Arabiyah) to the Development of Arabic Communication Skills at OCEAN Kediri - Abidah, Zakiyatul; Chebaiki , Hana (Sekolah Tinggi Ilmu Syrari’ah Daru ‘Ulum (STSDU) Lampung Timur., 2024)
This study aims to examine the implementation of the Arabic language environment (bi’ah ‘arabiyah) in developing Arabic communication skills at OCEAN Kediri. The research employed a descriptive qualitative approach, utilizing participatory observation, in-depth interviews with instructors and students, and documentation of learning activities as data collection methods. The findings indicate that the institution applies integrated strategies, including environmental visualization, the use of incentives and sanctions, learning group arrangements, daily habituation, extracurricular activities, and teacher modeling as a language role model. These strategies proved effective in enhancing the four core language skills: speaking, listening, reading, and writing, as well as improving communicative spontaneity, self-confidence, and student motivation. The consistent integration of the Arabic language environment facilitates the internalization of Arabic into daily activities. The study emphasizes the importance of bi’ah ‘arabiyah as a communicative, contextual, and sustainable learning model. The findings provide practical implications for Arabic language education institutions to create authentic learning environments that support the development of communicative competence and foster a consistent culture of Arabic language use